Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To find the zeros of the quadratic equation [tex]\( y = x^2 + 6x - 4 \)[/tex] by completing the square, follow these steps:
1. Start with the given quadratic equation:
[tex]\[ x^2 + 6x - 4 = 0 \][/tex]
2. Move the constant term to the other side of the equation:
[tex]\[ x^2 + 6x = 4 \][/tex]
3. To complete the square on the left side, we need to add and subtract the square of half the coefficient of [tex]\(x\)[/tex]. The coefficient of [tex]\(x\)[/tex] is 6, so half of it is 3, and its square is 9. Thus, we add and subtract 9:
[tex]\[ x^2 + 6x + 9 - 9 = 4 \][/tex]
4. Rewrite the equation by grouping the perfect square trinomial and the constant terms:
[tex]\[ (x + 3)^2 - 9 = 4 \][/tex]
5. Simplify by isolating the perfect square:
[tex]\[ (x + 3)^2 = 4 + 9 \implies (x + 3)^2 = 13 \][/tex]
6. Take the square root of both sides:
[tex]\[ x + 3 = \pm \sqrt{13} \][/tex]
7. Solve for [tex]\(x\)[/tex] by isolating it on one side:
[tex]\[ x = -3 \pm \sqrt{13} \][/tex]
Therefore, the zeros of the quadratic equation [tex]\( y = x^2 + 6x - 4 \)[/tex] are:
[tex]\[ x = -3 \pm \sqrt{13} \][/tex]
Hence, the correct answer is:
[tex]\[ \boxed{A. \; x=-3 \pm \sqrt{13}} \][/tex]
The result matches the choice A in the provided options.
1. Start with the given quadratic equation:
[tex]\[ x^2 + 6x - 4 = 0 \][/tex]
2. Move the constant term to the other side of the equation:
[tex]\[ x^2 + 6x = 4 \][/tex]
3. To complete the square on the left side, we need to add and subtract the square of half the coefficient of [tex]\(x\)[/tex]. The coefficient of [tex]\(x\)[/tex] is 6, so half of it is 3, and its square is 9. Thus, we add and subtract 9:
[tex]\[ x^2 + 6x + 9 - 9 = 4 \][/tex]
4. Rewrite the equation by grouping the perfect square trinomial and the constant terms:
[tex]\[ (x + 3)^2 - 9 = 4 \][/tex]
5. Simplify by isolating the perfect square:
[tex]\[ (x + 3)^2 = 4 + 9 \implies (x + 3)^2 = 13 \][/tex]
6. Take the square root of both sides:
[tex]\[ x + 3 = \pm \sqrt{13} \][/tex]
7. Solve for [tex]\(x\)[/tex] by isolating it on one side:
[tex]\[ x = -3 \pm \sqrt{13} \][/tex]
Therefore, the zeros of the quadratic equation [tex]\( y = x^2 + 6x - 4 \)[/tex] are:
[tex]\[ x = -3 \pm \sqrt{13} \][/tex]
Hence, the correct answer is:
[tex]\[ \boxed{A. \; x=-3 \pm \sqrt{13}} \][/tex]
The result matches the choice A in the provided options.
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.